Experiences of Integration of HIV, Hepatitis, and Sexually Transmitted Infection Services Across Different Countries Worldwide: A Scoping Review - Parya Jangipour Afshar; Vahid Yazdi‐Feyzabadi; Zahra Abdolahinia; AliAkbar Haghdoost; Reza Goudarzi; Katayoun Tayeri; Babak Eshrati; Hamid Sharifi (Health Science Reports, 2026)
ABSTRACT Background and Aims Integrating services for diseases appears to improve healthcare access and outcomes. This scoping review aimed to evaluate how different countries implement the integration of HIV, viral hepatitis, and sexually transmitted infection (STI) services. Methods This scoping review follows Arksey and O'Malley's five‐step framework. We searched PubMed, Scopus, and Web of Science until April 2025, with no limitations in languages and time. We also searched gray literature and manually searched reference lists to identify additional relevant studies. We included studies that met the eligibility requirements and extracted the information. Results Seventy‐eight articles met the eligibility criteria. The findings indicated that most integration efforts (93.5%) follow a vertical model. Integrated services were identified in North America, East and South Asia, Western and Southern Europe, Southern Africa, Southeast and Central Australia. The most commonly integrated services were STIs and HIV programs, followed by HCV and HIV. Conclusion While significant progress has been made in integrating services, efforts must be expanded to low‐ and middle‐income countries to reduce disease burden further and align with WHO targets. Strengthening regulatory frameworks and adopting context‐specific models could enhance the effectiveness of integration initiatives.